Incidence, risk factors and outcomes of submacular haemorrhage with loss of vision in neovascular age‐related macular degeneration in daily clinical practice: data from the FRB! registry. Issue 8 (23rd March 2022) - Gabrielle, Pierre‐Henry; Maitrias, Samuel; Nguyen, Vuong; Arnold, Jennifer J; Squirrell, David; Arnould, Louis; Sanchez‐Monroy, Jorge; Viola, Francesco; O'Toole, Louise; Barthelmes, Daniel; Creuzot‐Garcher, Catherine; Gillies, Mark; et al.
Abstract: Purpose: The main purpose of the study was to report the estimated incidence, cumulative rate, risk factors and outcomes of submacular haemorrhage (SMH) with loss of vision in neovascular age‐related macular degeneration (nAMD) receiving intravitreal injections (IVT) of vascular endothelial growth factor (VEGF) inhibitor in routine clinical practice. Methods: Retrospective analysis of treatment‐naïve eyes receiving IVTs of VEGF inhibitors (ranibizumab, aflibercept or bevacizumab) for nAMD from 1 January 2010 to 31 December 2020 that were tracked the Fight Retinal Blindness! registry. Estimated incidence, cumulative rate and hazard ratios (HR) of SMH with loss of vision during treatment were measured using the Poisson regression, Kaplan–Meier survival curves and Cox proportional hazard models. Results: We identified 7642 eyes (6425 patients) with a total of 135 095 IVT over a 10‐year period. One hundred five eyes developed SMH with loss of vision with a rate of 1 per 1283 injections (0.08% 95% confidence interval [95% CI] [0.06; 0.09]). The estimated incidence [95% CI] was 4.6 [3.8; 5.7] SMH with loss of vision per year per 1000 treated patients during the study. The cumulative [95% CI] rate of SMH per patient did not increase significantly with each successive injection (p = 0.947). SMH cases had a mean VA drop of around 6 lines at diagnosis, which then improved moderately to a 4‐line loss at 1 year. Conclusions: Submacular haemorrhage (SMH) with loss of vision is an uncommon complication that can occur at any time in eyes treated for nAMD in routine clinical practice, with only limited recovery of vision 1 year later.